Venetoclax plus intensive chemotherapy with cladribine, idarubicin, and cytarabine in patients with newly diagnosed acute myeloid leukaemia or high-risk myelodysplastic syndrome: a cohort from a single-centre, single-arm, phase 2 trial. Issue 8 (August 2021) - Kadia, Tapan M; Reville, Patrick K; Borthakur, Gautam; Yilmaz, Musa; Kornblau, Steven; Alvarado, Yesid; Dinardo, Courtney D; Daver, Naval; Jain, Nitin; Pemmaraju, Naveen; Short, Nicholas; Wang, Sa A; et al.
Summary: Background: Addition of the BCL2 inhibitor venetoclax to lower intensity therapy has been shown to improve overall survival in older (aged 75 years or older) and unfit patients with newly diagnosed acute myeloid leukaemia. The aim of this study was to investigate the activity of venetoclax combined with intensive chemotherapy in patients aged 65 years or younger with acute myeloid leukaemia. Methods: This cohort study was done at the MD Anderson Cancer Center in the USA, as part of the single-centre, single arm, phase 2, CLIA trial. Here we report on the independent cohort investigating the safety and activity of venetoclax added to intensive chemotherapy (the CLIA regimen [cladribine, high-dose cytarabine, idarubicin]). Eligible patients were aged 18–65 years with a new diagnosis of acute myeloid leukaemia, mixed phenotype acute leukaemia, or high-risk myelodysplastic syndrome (≥10% blasts or International Prognostic Scoring System ≥2 [intermediate]), who received no previous potentially curative therapy for leukaemia. Patients received cladribine (5 mg/m 2 ) and cytarabine (1·5 g/m 2 for patients aged <60 years, 1 g/m 2 for patients aged ≥60 years) intravenously on days 1–5 and idarubicin (10 mg/m 2 ) intravenously on days 1–3. Consolidation was cladribine (5 mg/m 2 ) and cytarabine (1 g/m 2 for patients aged <60 years and 0·75 g/m 2 for patients aged ≥60 years) on days 1–3 and idarubicin (8 mg/m 2 ) on days 1–2. Venetoclax (400 mg) was given on days 2–8 with each course. Patients with a known FLT3-ITD or FLT3-TKD mutation received midostaurin or gilteritinib. The primary outcome was composite complete response (complete response plus complete response with incomplete blood count recovery). Secondary outcomes were overall response, duration of response, event-free survival, overall survival, and safety. This trial was registered with ClinicalTrials.gov, NCT02115295. Findings: Between Feb 25, 2019, and March 23, 2021, 77 patients were assessed for eligibility, 50 of whom were enrolled. Median age was 48 years (IQR 37–56). 47 (94% [95% CI 83–98]) patients had composite complete response, with the same proportion also having an overall response; two (4% [1–14]) patients did not respond, and one (2% [0–11]) patient died during induction. 37 (82% [95% CI 68–92]) of 45 patients had undetectable measurable residual disease (MRD). At a median follow-up of 13·5 months (IQR 6·4–19·5), the median duration of response, event-free survival, and overall survival were not reached. At 12 months, the estimated duration of response was 74% (95% CI 60–92), event-free survival was 68% (54–85), and overall survival was 85% (75–97). The most common adverse events of grade 3 or worse were febrile neutropenia (42 [84%] patients), infection (six [12%]), and alanine aminotransferase elevations (six [12%]). There was one death during induction in a patient treated with CLIA–venetoclax plus a FLT3 inhibitor. Two patients died of infectious complications while in complete response in consolidation cycles, both of whom had FLT3 -mutated acute myeloid leukaemia and were receiving combined therapy with a FLT3 inhibitor. No deaths were deemed to be treatment related. Interpretation: Venetoclax added to CLIA was safe and active in patients with newly diagnosed acute myeloid leukaemia or high-risk myelodysplastic syndrome, producing high rates of durable MRD-negative remissions and encouraging event-free survival and overall survival. Funding: MD Anderson Cancer Center.